Effect of W self-implantation and He plasma exposure on early-stage defect and bubble formation in tungsten. (18th April 2018) - Thompson, M.; Drummond, D.; Sullivan, J.; Elliman, R.; Kluth, P.; Kirby, N.; Riley, D.; Corr, C.S.
Abstract: To determine the effect of pre-existing defects on helium-vacancy cluster nucleation and growth, tungsten samples were self-implanted with 1 MeV tungsten ions at varying fluences to induce radiation damage, then subsequently exposed to helium plasma in the MAGPIE linear plasma device. Positron annihilation lifetime spectroscopy was performed both immediately after self-implantation, and again after plasma exposure. After self-implantation vacancies clusters were not observed near the sample surface (<30 nm). At greater depths (30–150 nm) vacancy clusters formed, and were found to increase in size with increasing W-ion fluence. After helium plasma exposure in the MAGPIE linear plasma device at 300 K with a fluence of 10 23 He-m −2, deep (30–150 nm) vacancy clusters showed similar positron lifetimes, while shallow (<30 nm) clusters were not observed. The intensity of positron lifetime signals fell for most samples after plasma exposure, indicating that defects were filling with helium. The absence of shallow clusters indicates that helium requires pre-existing defects in order to drive vacancy cluster growth at 300 K. Further samples that had not been pre-damaged with W-ions were also exposed to helium plasma in MAGPIE across fluences from 1 × 10 22 to 1.2 × 10 24 He-m −2 . Samples exposed to fluences up to 1 × 10 23 He-m −2 showed no signs of damage. Fluences of 5 × 10 23 He-m −2 and higher showed significant helium-cluster formation within the first 30 nm, with positron lifetimes in the vicinity 0.5–0.6 ns. The sample temperature was significantly higher for these higher fluence exposures ( 400 K) due to plasma heating. This higher temperature likely enhanced bubble formation by significantly increasing the rate interstitial helium clusters generate vacancies, which is we suspect is the rate-limiting step for helium-vacancy cluster/bubble nucleation in the absence of pre-existing defects.